Factor of cannibalism in guinea pigs when planning long-term experiments in phthisiatrics - Sosnytska, A. O.; Sosnitskaya, Alona; Sosnitskaya, A. A.; Сосницька, Альона Олександрівна (Одеський ДАУ, 2024)
Cannibalism, as a general biological phenomenon inherent in carnivorous and omnivorous animals, from mice to humans, is well known. Cases of cannibalism have been described even in such large and dangerous predators as bears, and eating their own kind in mice, rats and pecking in chickens are banal phenomena in zooecology and are widespread. However, practical observations of the behavior of guinea pigs during a period of long quarantine and rearing when preparing animals for a bioassay for tuberculosis showed the presence of unmotivated cruelty and fatal fights with subsequent cannibalism. Канібалізм, як загальнобіологічне явище, властиве хижим і всеїдним тваринам, від миші до людини, добре відомий. Випадки канібалізму описані навіть у таких великих і небезпечних хижаків, як ведмеді, а поїдання собі подібних у мишей, щурів і клювання у курей - банальні явища в зооекології і широко поширені. Однак практичні спостереження за поведінкою морських свинок в період тривалого карантину і вирощування при підготовці тварин до біопроби на туберкульоз показали наявність невмотивованої жорстокості і смертельних бійок з подальшим канібалізмом.
Фактори канібалізму морських свинок при плануванні довгострокових експериментів у фтизіатрії
Keywords: guinea pigs; морські свинки; cannibalism; канібалізм; bioassay; біопроба